(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2024)
FORGOTTEN TRANSLATIONS OF AMERICAN POETS FROM THE PEN OF ISIDORA SEKULIĆ Urged by writer Marko Ristić, the renowned Serbian author and the first woman in the Serbian Academy of Sciences and Arts, Isidora Sekulić (1877–1958) translated five poems by five American poets for Mr Ristić’s journal “Putevi” (“Roads”), published in Belgrade in 1924. Mr Ristić selected two of them to be published in the journal, while the rest were found in Mr Ristić’s estate, unpublished to this day. The author of this paper presented in this paper the three Ms Sekulić’ translations (of poems written by N. V. Lindsay, R. Frost, and W. De la Mare) from Mr Ristić’s archive.